Prevalence of syphilis and risk factors among HIV-positive men who have sex with men in Guangdong province - Peizhen Zhao; Peizhen Zhao; Ziying Yang; Ye Zhang; Jinmei Chen; Xuezhen Fu; Weiming Tang; Weiming Tang; Jiyuan Zhou; Jiyuan Zhou (Frontiers Media S.A., 2022)
BackgroundHIV-positive men who have sex with men (MSM) tend to have high syphilis incidence. Our objective is to evaluate the prevalence of syphilis and determine the risk factors of syphilis among HIV-positive MSM.MethodsA cross-sectional study with convenience sampling was performed among HIV-positive MSM in six cities of Guangdong Province from June 2020 to August 2021. Participants completed a survey including social-demographic characteristics, sexual behaviors and self-reported syphilis, chlamydia, gonorrhea, herpes, human papillomavirus statuses after HIV diagnosis. Multivariate logistic regression was used to determine the factors associated with syphilis and sexually transmitted diseases (STD).ResultsAmong 944 HIV-positive MSM, 141 (14.9, 95% CI: 12.7-17.2%) men had syphilis and 220 (23.3, 95% CI: 20.6-26.0%) men had STD. Multivariate analysis indicated that MSM who met male sexual partners mainly through traditional meeting places (spa or bath house, sauna, foot or body massage parlor) in the last 6 months [adjusted Odds Ratio (aOR) = 2.91, 95% CI: 1.09-7.79], and who were diagnosed with herps after the HIV diagnosis (aOR = 3.79, 95% CI: 1.16-12.39) were more likely to have syphilis. In addition, MSM who met male sexual partners mainly through traditional meeting places in the last 6 month (aOR = 2.55, 95% CI: 1.01-6.42), and who had more than one male sexual partner in the last 6 months (aOR = 1.88, 95% CI: 1.17-3.02) were more likely to have STD.ConclusionsThe prevalence of syphilis and other STDs is relatively high among HIV-positive MSM in southern China. Routine syphilis screening as a part of HIV monitoring among HIV-positive MSM will have important epidemiological significance for the management of infected patients, and can help reduce the spread of syphilis.